Intelligent Robotics and Applications : 12th International Conference, ICIRA 2019, Shenyang, China, August 8–11, 2019, Proceedings, Part VI /: 12th International Conference, ICIRA 2019, Shenyang, China, August 8–11, 2019, Proceedings, Part VI. (2019) - Unknown
No abstract available